Patterns and Outcomes of Patient Complaints Against Urologists: A Seven-Year Retrospective Analysis in Iran - Shahrokhi, Mahzad; Behnam Shakiba; Ameri, Maryam; Ali Mohammadi, Ali Mohammad; Vahedi, Vahid (Urology Journal, 2026)
We conducted a retrospective cross-sectional analysis of 288 complaints filed against urologists between 2017 and 2023 at the Forensic Medicine Organization in Shemiranat, Tehran. The number of complaints increased steadily, peaking in 2023 (n = 66) and reaching a nadir in 2020 (n = 13), likely reflecting the impact of the COVID-19 pandemic. Most complainants were male (89.6%), and patients aged >60 years comprised the largest group (31.3%). Complaints were overwhelmingly directed at specialist urologists (97.6%), with subspecialists accounting for only 2.4%. Cases more frequently originated from public hospitals (66.3%) than from private institutions (33.7%).